The Influence of Work Stress, Rewards and Punishments on Organizational Commitment with Work Conflict as an Intervening Variable in the Department of Public Works and Spatial Planning in Binjai City - admin, admin; Isa Indrawan, Muhammad (CV. Lafadz Jaya, 2023)
Within the organization, creating quality human resources capable of possessing skills and high competitiveness is an important factor in global competition. This study was to analyze the effect of work stress, rewards and punishments on organizational commitment with work conflict as an intervening variable. This research was conducted at the Office of Public Works and Spatial Planning in Binjai City. The population in this study was 79 employees. Sampling using a saturated sample (79 employees). The research model is path analysis and uses Smart PLS 3.3.3 as a measuring tool. The results of this study are Rewards have no significant positive effect on Organizational Commitment. Prizes have no significant positive effect on work conflict. Punishment has no significant positive effect on Organizational Commitment. Punishment has no significant positive effect on work conflict. Work Conflict has a positive and significant effect on Organizational Commitment. Work Stress has no significant negative effect on Organizational Commitment. Work Stress has no significant positive effect on Perna Conflict. Prizes have no significant positive effect on Organizational Commitment through Work Conflict. Punishment has no significant positive effect on Organizational Commitment through Work Conflict. Work Stress has no significant positive effect on Organizational Commitment through Work Conflict.